Brine shrimp lethality bioassay of Glaucium grandiflorum var. grandiflorum - (:unkn) unknown (My University, 2007)
Alkaloidal extracts of the aerial parts of the samples of Glaucium grandiflorum Boiss. et Huet var. grandiflorum collected from three different parts of Turkey and their major alkaloids allocryptopine, protopine, (+)-isocorydine, (+)-corydine were screened for their cytotoxicity using brine shrimp lethality test. All the samples of Glaucium grandiflorum var. grandiflorum displayed significant cytotoxic activity. Allocryptopine, protopine, (+)-isocorydine, (+)-corydine showed potent activity with LC50 values 15.92, 37.51, 237.24, 75.95, respectively.